Macrocycle supported dimetallic lanthanide complexes with slow magnetic relaxation in Dy2 analogues. Issue 40 (7th October 2020) - Shen, Fu-Xing; Pramanik, Kuheli; Brandão, Paula; Zhang, Yi-Quan; Jana, Narayan Ch.; Wang, Xin-Yi; Panja, Anangamohan
Abstract : A series of isomorphous dimetallic Ln III complexes with a macrocycle ligand and different β-diketone coligands have been synthesized and characterized structurally and magnetically. Abstract : Six dimetallic lanthanide complexes, [Ln2 (L′)(acac)4 ] (1Dy –3Gd ) (Ln = Dy (1Dy ), Tb (2Tb ) and Gd (3Gd )) and [Ln2 (L′)(tfac)4 ] (4Dy –6Gd ) (Ln = Dy (4Dy ), Tb (5Tb ) and Gd (6Gd )) (H2 L′ = 1, 9-dichloro-3, 7, 11, 15-tetraaza-1, 9(1, 3)-dibenzenacyclohexadecaphane-2, 10-diene-1, 9-diol), have been synthesized by the reaction of lanthanide nitrates with the HL ligand in the presence of acetylacetonate (acac) (or trifluoroacetylacetonate (tfac) and triethylamine (HL = 4-chloro-2, 6-bis(-((3-((3-(dimethylamino)propyl)amino)propyl)imino)methyl)phenol). Ln-Assisted modification of the Schiff base HL occurred and led to the formation of a new macrocyclic ligand (H2 L′). X-ray crystallographic analysis revealed that the Ln III ions of complexes 1Dy –6Gd are all eight-coordinated in a square antiprismatic geometry with D 4d local symmetry. Magnetic measurements of these complexes revealed that 1Dy and 4Dy show single-molecule magnet behaviour with energy barriers of 66.7 and 79.0 K, respectively, under a zero direct magnetic field. The orientations of the magnetic axes and crystal field parameters were obtained from theoretical calculations and an electrostatic model. The magneto-structural correlations of SMMs 1Dy and 4Dy are further discussed in detail.